2010
DOI: 10.1248/bpb.33.146
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Signal Transducer and Activator of Transcription 6 (STAT6) and STAT1, but Not STAT3, Induced by Antigen Inhalation in Bronchial Smooth Muscles of Sensitized Mice

Abstract: The dramatic increase in the number of asthma cases over the last decades is of great concern for public health in the world.1) The CD4 ϩ T helper 2 lymphocytes (Th2 cells) are closely associated with disease severity, suggesting an integral role of Th2 cells in the pathophysiology of allergic bronchial asthma.2-5) Th2 cells secrete various cytokines, termed Th2 cytokines, which cause several key features of allergic bronchial asthma, including airway hyperresponsiveness (AHR).2-5) Increasing evidence indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Although the levels of p-STAT1 and p-STAT3 were not significantly increased in our ECRS model, STAT1 and STAT3 were also previously considered potential targets for regulating airway inflammation. 18 20 STAT1 is critical for Th1 polarization, and its hallmark cytokine is IFN-γ, one of the Th1 cytokines. 40 However, no evidence of elevated IFN-γ levels was reported in AR or ECRS, although a previous study suggested that epithelial STAT1 was activated in asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the levels of p-STAT1 and p-STAT3 were not significantly increased in our ECRS model, STAT1 and STAT3 were also previously considered potential targets for regulating airway inflammation. 18 20 STAT1 is critical for Th1 polarization, and its hallmark cytokine is IFN-γ, one of the Th1 cytokines. 40 However, no evidence of elevated IFN-γ levels was reported in AR or ECRS, although a previous study suggested that epithelial STAT1 was activated in asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Cui et al 44 reported that elevated expression of STAT3 led to the overexpression of IgE and other inflammatory factors in an OVA-induced AR model. However, Chiba et al 19 suggested that STAT3 phosphorylation could not be induced by antigens in the lungs of a mouse asthma model. Further studies are needed to define the functional roles of STAT1 and STAT3 in ECRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT6 has been demonstrated to regulate many pathologic features of lung inflammatory responses in animal models including airway eosinophilia, epithelial mucus production, smooth muscle changes, Th2 cell differentiation, and IgE production from B cells (Walford and Doherty, 2013). Also, a significant increase of STAT6 phosphorylation was observed in mice with allergic bronchial asthma (Chiba et al, 2010). Especially, Th2-dependent JAK/STAT activation pathway plays a critical role in the exacerbation of asthma.…”
Section: Discussionmentioning
confidence: 99%